Safety Assessment Approach of Hazard and Operability (HAZOP) In A Power Plant Sector - Akmal Suryadi; Mega Cattleya PA Islami; Gilang Ramadhan (Nusantara Science and Technology Proceedings, 2023)
In line with the current development of society, the need for electricity can be said to be a primary need that must be met to support community activities, both for economic purposes and to fulfill daily household needs. The research was conducted at one of the power generation companies. Based on the results of initial observations and interviews with workers at the company, it was explained that the potential danger of work accidents in the boiler machine area at the Steam-Electric Power Station was considered high. Dangers of work accidents that can occur in the boiler area include hot weather, noise, sparks, water vapor leaks, contact with hot steam pipes, high pressure, slipping, and falling from heights. The danger that has occurred in the boiler machine area is noise, noise often occurs because workers underestimate the use of earplugs or earmuffs because they feel they often work without using earplugs. This research aims to analyze the potential dangers of work accidents in the PLTU boiler machine area in the company. Analysis of potential accident hazards was carried out using the HAZOP method. It is hoped that the HAZOP method will enable researchers to know the dangers and how to overcome them to minimize the risk of occupational hazards. This method has the advantage that work using this method will run systematically, the results obtained are more detailed compared to other methods and can be used in various systems. The results of the research show that the risk of danger in power generation companies amounts to 12 potential work accident hazards. Potential dangers of work accidents consist of deafness (25%), burns (17%), slips (9%), shortness of breath (9%), dehydration (8%), electric shock (8%), pinching (8%), fire (8%), and corrosion (8%).